The Role of Health Risk Assessment Techniques in Controlling Air Pollution: A Mini Review - Kiaei , Reza; Pardakhti, Alireza; Zahed , Mohammad Ali (Health Nexus, 2024)
Health risk assessment is a method that can be used to determine the potential effects of a risk on the well-being of an individual, a group of individuals, or a whole community. In order to comprehend the potential adverse impacts on health, factual and technical information is employed. In the current mini-review, the updated publications regarding the issue of HRA are systematically reviewed based on the performance and purposes. The main sources of extracting paper are Elsevier and Springer in the Google Scholar and Sience Direct. Volatile Aromatic Hydrocarbons (VAHs) are a significant cause of pollution in petrochemical and petroleum refineries. It is a known human carcinogen, and epidemiological investigations have demonstrated that it, even at low doses, contributes to the development of both acute and chronic leukemia. Chronic exposure to high levels of benzene can result in more serious negative health effects like blood illness, haematotoxicity, genotoxicity, an increase in persistent chromosome aberrations, problems with reproduction, and mortality. Acute exposure to high levels of benzene can also affect the brain and spinal cord and cause headaches, nausea, and dizziness. The importance of HRA in the refinery industry is highlighted in the previous works. However, the use of Artifical Intelligence techniques has been rarely considered as an approach. The gaps and shortcomings obtained in this review can be starting point for the future investigations.